The System of Career Promotion in Libyan law (The International Journal for Scientific Research, 2023)
The researcher noted through his work in the legal department of the university and also through his teaching of the courses of administrative law and the administrative judiciary of the Faculty of Law، that there are many problems related to career promotions for employees in all organizations، And due to the nature of these decisions, the discretion and rights of the staff member overlap, which puts the general authority in between applying administrative justice and the granting of functional rights.In this paper, the researcher discussed the basic conditions set by the legislator for promotion as well as administrative and judicial oversight of the administration's actions. In particular، through extrapolation of legal texts and judicial decisions, the administrative procedures used by the Department for the granting of career promotions were studied as well as the problems associated with these decisions and what guarantees are approved by the legislator to ensure that the Department does not deviate its authority from the public good. Also, judicial guarantees for employees' access to their occupational rights, this was done in two researches: the first is about the definition of promotion and its conditions and the second is about the administrative and judicial safeguards for career promotion.
Keywords: Libyan; Law; Employee; Promotion; Guarantees; Judicial; Efficiency